Perceived stress, quality of life, and their correlation amongst undergraduate pharmacy students: findings from public university in Malaysia - Fata Nahas, Abdul Rahman; Elkalmi, Ramadan Mohamed Mahmod; Al-Shami, Abdulkareem Mohammed; Elsayed, Tarek Mohamed Ali (Wolters Kluwer - Medknow, 2020)
Stress as a psychological disorder might affect an individual’s physical, mental and emotional aspects at any age. Although university students who experience acute stress still can adapt to it; however, chronic stress may lead to substantial issues. It has been reported that health-related university studies convey a high level of stress, which could adversely affect students’ health as well as their quality of life (QOL), and pharmacy is no exception. Objectives: The aims of the study were to evaluate the stress level and its correlation with QOL among pharmacy students. Materials and Methods: Ina cross-sectional study, all undergraduate students (N = 456] of Faculty of Pharmacy, International Islamic University Malaysia, were planned to be surveyed. The stress level was evaluated using Perceived Stress Scale (PSS), whereas World Health Organization QOL questionnaire (WHOQOL-BREF] was used for QOL measuring. Descriptive and inferential analyses were run using SPSS Version 21.0. Results: Of the 277 students responded (72.2% females], 68.9% were moderately stressed (M = 21.9 ± 6.4], No significant differences in PSS score were found between different years of study (p = 0.75], A significant negative correlation was also observed between PSS score and WHOQOL-BREF score ip < 0.001], Conclusion: Although it is of moderate intensity, perceived stress can negatively impact pharmacy student’s QOL, therefore, counselling sessions should be considered throughout the years of pharmacy study.